2012
DOI: 10.3892/or.2012.1870
|View full text |Cite
|
Sign up to set email alerts
|

Natural chalcones as dual inhibitors of HDACs and NF-κB

Abstract: Histone deacetylase enzymes (HDACs) are emerging as a promising biological target for cancer and inflammation. Using a fluorescence assay, we tested the in vitro HDAC inhibitory activity of twenty-one natural chalcones, a widespread group of natural products with well-known anti-inflammatory and antitumor effects. Since HDACs regulate the expression of the transcription factor NF-κB, we also evaluated the inhibitory potential of the compounds on NF-κB activation. Only four chalcones, isoliquiritigenin (no. 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 42 publications
1
39
0
1
Order By: Relevance
“…In compound 5 the introduction of an electron donor group -OH at position C8 and an electron withdrawing group -Br at C6 contributes to red shi the transition. With the exception of 7 all the other newly systems (6,(8)(9)(10)) that contain several substituents show signicant red shis.…”
Section: Uv-vis Spectramentioning
confidence: 96%
“…In compound 5 the introduction of an electron donor group -OH at position C8 and an electron withdrawing group -Br at C6 contributes to red shi the transition. With the exception of 7 all the other newly systems (6,(8)(9)(10)) that contain several substituents show signicant red shis.…”
Section: Uv-vis Spectramentioning
confidence: 96%
“…Isoliquiritigenin (11), butein (45) and homobutein (49) have been reported to inhibit not only histone deacetylase activity but TNF-a induced NF-jB activity as well. SAR studies showed that hydroxy groups at the 2 0 -, 4 0 -, 3-and 4-positions were important for dual activity of the compounds (Orlikova et al 2012).…”
Section: Chemoprevetive Properties Of Natural Chalconesmentioning
confidence: 99%
“…Sharp structure–activity relationships (SAR) have been observed, suggesting a well‐defined interaction between chalcones and the responsible cellular target for cytotoxicity . A number of putative targets have been proposed, including tubulin , several kinases , cathepsins , topoisomerases , MDM2 , and many others . However, data to date are far from sufficient to suggest any direct interactions of chalcones with these targets in cells.…”
Section: Introductionmentioning
confidence: 99%